Self‐Efficacy and Social Support are Associated with Disability for Ambulatory Prosthesis Users After Lower‐Limb Amputation. Issue 5 (14th September 2020) - Miller, Matthew J.; Cook, Paul F.; Magnusson, Dawn M.; Morris, Megan A.; Blatchford, Patrick J.; Schenkman, Margaret L.; Christiansen, Cory L.
Abstract : Background: Interventions targeting psychosocial factors may improve rehabilitation outcomes for prosthesis users after lower‐limb amputation (LLA), but there is a need to identify targeted factors for minimizing disability. Objective: To identify psychosocial factors related to disability for prosthesis users after LLA in middle age or later. Design: Cross‐sectional study. Setting: General community. Participants: Participants with LLA (N = 122) were included in this cross‐sectional study if their most recent LLA was at least 1 year prior, they were ambulating independently with a prosthesis, and they were between 45 and 88 years old. Interventions: Not applicable. Main Outcome Measures: Disability, the primary outcome, was measured using the World Health Organization Disability Assessment Schedule 2.0 (WHODAS). Candidate psychosocial variables included self‐efficacy, social support, and motivation, measured using the Self‐Efficacy of Managing Chronic Disease questionnaire (SEMCD), Multidimensional Scale of Perceived Social Support questionnaire (MSPSS), and modified contemplation ladder (mCL), respectively. The hypothesis was that greater self‐efficacy, social support, and motivation would be associated with lower disability when controlling for covariates. Results: The covariate model, including etiology, age, sex, U.S. military veteran status, LLA characteristics, time since LLA, medical complexity, and perceived functional capacity, explained 66.1% of disability variability (WHODAS 2.0). Backward elimination of candidate psychosocial variables stopped after removal of motivation ( P  = .10), with self‐efficacy ( P  < .001) and social support ( P  = .002) variables remaining in the final model. The final model fit was statistically improved ( P  < .001) and explained an additional 6.1% of disability variability when compared to the covariate model. Conclusions: Greater self‐efficacy and social support are related to lower disability after LLA. Findings suggest there may be a role for interventions targeting increased physical function, self‐efficacy, and social support for ambulatory prosthesis users after LLA in middle age or later, especially when complicated by multiple chronic conditions.